The Protein Tyrosine Phosphatase Shp2 Is Required for the Generation of Oligodendrocyte Progenitor Cells and Myelination in the Mouse Telencephalon - Ehrman, Lisa A. (Society for Neuroscience, 2014)
The protein tyrosine phosphatase Shp2 (PTPN11) is crucial for normal brain development and has been implicated in dorsal telencephalic neuronal and astroglia cell fate decisions. However, its roles in the ventral telencephalon and during oligodendrogenesis in the telencephalon remain largely unknown. Shp2 gain-of-function (GOF) mutations are observed in Noonan syndrome, a type of RASopathy associated with multiple phenotypes, including cardiovascular, craniofacial, and neurocognitive abnormalities. To gain insight into requirements for Shp2 (LOF) and the impact of abnormal Shp2 GOF mutations, we used a Shp2 conditional mutant allele (LOF) and a cre inducible Shp2-Q79R GOF transgenic mouse in combination with Olig2(cre/+) mice to target embryonic ventral telencephalic progenitors and the oligodendrocyte lineage. In the absence of Shp2 (LOF), neuronal cell types originating from progenitors in the ventral telencephalon were generated, but oligodendrocyte progenitor cell (OPC) generation was severely impaired. Late embryonic and postnatal Shp2 cKOs showed defects in the generation of OPCs throughout the telencephalon and subsequent reductions in white matter myelination. Conversely, transgenic expression of the Shp2 GOF Noonan syndrome mutation resulted in elevated OPC numbers in the embryo and postnatal brain. Interestingly, expression of this mutation negatively influenced myelination as mice displayed abnormal myelination and fewer myelinated axons in the white matter despite elevated OPC numbers. Increased proliferating OPCs and elevated MAPK activity were also observed during oligodendrogenesis after expression of Shp2 GOF mutation. These results support the notion that appropriate Shp2 activity levels control the number as well as the differentiation of oligodendrocytes during development.